Di Balik Meja Biliar: Score Girl dan Sisi Gelap Prostitusi di Kota Banjarmasin - Afifah, Siti; An'amta, Dimas Asto Aji (Prodi Sosiologi FISIP ULM, 2026)
The practice of covert prostitution in entertainment venues such as billiard halls often occurs through the use of nonverbal symbols that are not explicitly acknowledged by the actors involved, particularly score girls. This study aims to analyze the symbols and meanings used by score girls in covert prostitution practices at a billiard venue in Banjarmasin City, South Kalimantan. This research employs a qualitative, phenomenological approach, using observation, in-depth interviews, and documentation. Data analysis was conducted using Miles and Huberman's interactive model. The findings indicate that score girls use symbols such as revealing clothing, body gestures, and verbal terms like “open,” “ST” (short time), and “LT” (long time) as implicit codes to subtly offer sexual services. These symbols are understood within a specific social context of nightlife entertainment venues. Through George Herbert Mead’s theory of symbolic interactionism, it was found that the concepts of mind, self, and society play a role in shaping the social identity of score girls and their role negotiation processes, where their actions are the result of symbolic meaning-making and ongoing social interactions. This research contributes to the reinforcement of symbolic interactionism theory and enriches public understanding of symbolic communication within covert social practices in entertainment settings. Future studies are expected to further explore the dynamics of symbolic interaction in covert prostitution practices in digital spaces or social media as an adaptation to technological developments in communication.